LEARNING DESIGN OF NETS CUBE AND SURFACE AREA OF CUBE USING MATS PUZZLE ON V GRADE I - Rahman, A; Zulkardi, Zulkardi; Somakim, Somakim
This is a design research. This research aims at making a learning trajectory on nets of cube and surface area of cube by using mats-puzzle. This research was use â€œPendidikan Matematika Realistik Indonesia (PMRI)â€ approached. 17 students in the fifth grade of My School primary school had participated in this research. This research was by means of preliminary design, design experiment (pilot & teaching experiment), and retrospective analysis. Data collections were generated from observing the students, interviewing the students, collecting student works, and taking photos and videos of the students activities. The designed HLT was compared with the studentsâ€™ Actual Learning Trajectory (ALT) during the teaching experiment. Retrospective analysis of teaching experiment indicated that the designed Learning Trajectory (LT) used mats-puzzle has helped students comprehended on nets of cube and surface area of cube.